Climate Change and Disaster Impacts on Rose Production: The Moderating Role of Farmer Institutions and Socioeconomic Characteristics - Muhammad Luthfie Fadhilah; Levana Masitajasmin Putri; Nur Indah Cahyaningtyas (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to analyze the factors affecting rose production, including climate and disaster impacts, farmer group membership, partnership, gender, age, and education. The research uses a quantitative approach with secondary data obtained from the Horticulture Household Survey (STH) conducted by the Central Java Bureau of Statistics, involving 107 farmers. Data were analyzed using multiple linear regression with the Ordinary Least Squares (OLS) method. The results show that, simultaneously, all independent variables significantly influence rose production, as indicated by the Prob(F-statistic) value of 0.0251 (< 0.05). However, partially, only age and education have a positive and significant effect on production, while climate and disaster impacts, farmer group membership, partnership, and gender do not show significant effects. These findings suggest that farmers’ human capital plays a more important role than environmental and institutional factors in determining production outcomes. The study implies that improving farmers’ education and experience is crucial to increasing productivity. Strengthening extension services and training programs is recommended to enhance farmers’ adaptive capacity and technical skills. Future research should include additional variables such as land size, input use, and technology adoption to provide a more comprehensive analysis. Keywords: climate change, farmer characteristics, partnership, regression analysis, rose production